TiO2/Eu3+ Thin Films with High Photoluminescence Emission Prepared by Electrophoretic Deposition from Nanoparticulate Sols. Issue 30 (4th September 2014) - Borlaf, Mario; Colomer, María T.; de Andrés, Alicia; Cabello, Fátima; Serna, Rosalia; Moreno, Rodrigo
Abstract: The light emission properties of anatase TiO2 /Eu 3+ thin films prepared by electrophoretic deposition and of the corresponding precursor nanoparticulate sols and xerogels with different Eu 3+ contents are reported. Transparent anatase TiO2 thin films were successfully obtained by electrophoretic deposition after dilution of the original sols with ethanol in order to inhibit the water hydrolysis and facilitate the drying process. The topography of the films shows a high homogeneous distribution in terms of grain size and roughness of the surface of the thin films. The film thickness varied from 50 nm to 800 nm and it was found to be strongly dependent on the Eu 3+ content of the sols, probably because of uncompensated electrical charges provided by Eu 3+ ions located at the surface of the nanoparticles. A spontaneous densification of the films occurs at a thickness above 400 nm and, concomitantly, a significant increase of the Eu 3+ emission efficiency is detected. Abstract : Transparent and nanoparticulate anatase TiO2 /Eu 3+ thin films were obtained by electrophoretic deposition. A densification of the films occurs at a thickness above 400 nm and, concomitantly, a significant increase of the Eu 3+ emission efficiency is detected. Similar values of PL efficiency to those of the xerogels (bulk material) could be achieved.